A conserved set of maternal genes? Insights from a molluscan transcriptome - Liu, M. Maureen; Davey, John W.; Jackson, Daniel J.; Blaxter, Mark L.; Davison, Angus (University of the Basque Country Press, 2014)
The early animal embryo is entirely reliant on maternal gene products for a ‘jump-start’ that transforms a transcriptionally inactive embryo into a fully functioning zygote. Despite extensive work on model species, it has not been possible to perform a comprehensive comparison of maternally-provisioned transcripts across the Bilateria because of the absence of a suitable dataset from the Lophotrochozoa. As part of an ongoing effort to identify the maternal gene that determines left-right asymmetry in snails, we have generated transcriptome data from 1 to 2-cell and ~32-cell pond snail (Lymnaea stagnalis) embryos. Here, we compare these data to maternal transcript datasets from other bilaterian metazoan groups, including representatives of the Ecydysozoa and Deuterostomia. We found that between 5 and 10% of all L. stagnalis maternal transcripts (~300-400 genes) are also present in the equivalent arthropod (Drosophila melanogaster), nematode (Caenorhabditis elegans), urochordate (Ciona intestinalis) and chordate (Homo sapiens, Mus musculus, Danio rerio) datasets. While the majority of these conserved maternal transcripts (“COMATs”) have housekeeping gene functions, they are a non-random subset of all housekeeping genes, with an overrepresentation of functions associated with nucleotide binding, protein degradation and activities associated with the cell cycle. We conclude that a conserved set of maternal transcripts and their associated functions may be a necessary starting point of early development in the Bilateria. For the wider community interested in discovering conservation of gene expression in early bilaterian development, the list of putative COMATs may be useful resource.